Russas nos circuitos de mudanças sob o signo da Dakota: experiências e sentidos do trabalho na vida das mulheres - Cruz, Rosilene de Sousa (2017)
The objective of this dissertation was to analyze how the policy of industrial decentralization reconfigured in the 1990s, after the Tasso Jereissati government in Ceará, modified the daily life of the city of Russas, with the arrival of the shoe factory Dakota Nordeste S / A, in 1998. In a specific way, as experiences in the world of work directly and indirectly imply the daily lives of women workers in the factory, when they enter distant territories of the metropolitan region of Fortaleza, which are marked by a work force tripod abundant, absence of industrial experience and almost no developed trade union base. "Jereissati era" is the watershed of this Ceará industrial policy, which, in turn, is responsible for the intensification of the urbanization process in interior cities, which receive industries with the intention of moving in search of greater profits. In fact, this industrial displacement for the municipalities of Ceará emerges a new category of workers. In this way, the new forms of sociability, in a rural way within the urban, that are cut out in the light of the categories of gender, implying social, economic, spatial and cultural changes are due to these economic transformations. The research was based on a field work interview with the factory's working women; employees who assumed managerial functions, supervision, programming and personal and administrative control of the company. As well as in secondary databases, by IBGE and information previously studied by other researchers. This study verified from the conditions put, a profile of people who enter the factory, many of them originating from rural experiences and customs; carry in themselves the mark of the absence and exception of the world of production; have low schooling and, therefore, low qualification. In this way, capital, by "letting this worker down on his knees", contests his subjectivity, making himself the choice of a better life than before. Without departing from the rule, Russas, visualized by the magnifying glass of capital, falls within this line of "new regions", with a category of workers, predominantly women, with labor rights flexibilized in the precariousness of the world of work, more rapidly, of the that the Brazilian legislation itself was able to regress.